Building Your Licensing and Negotiation Skills Toolkit. Issue 1 (18th May 2016) - Dygert, Claire; Barrett, Heather
Abstract : The advent of electronic resources brought about the need for license agreements between libraries and publishers. Many librarians today are new to licensing and negotiating with publishers, or have received limited training and education. Based on her years of licensing and negotiation experience, Clair Dygert of the Florida Virtual Campus (FLVC) provided librarians with practical advice and tools for working with licenses and negotiating with publishers, as well as encouragement for entering into these new areas. She included examples taken directly from FLVC's licensing guidelines and negotiation proposals and encouraged attendees to use those documents in creating their own local documents. She also drew on the book Getting to Yes: Negotiating Agreement Without Giving In by Roger Fisher and William Ury to describe principled bargaining as the most effective and constructive method of negotiation.